Implementation of antiretroviral therapy (ART) in former Soviet Union countries - Amangaldiyeva, Aidana; Davlidova, Salima; Baiserkin, Bauyrzhan; Dzissyuk, Natalya; DeHovitz, Jack; Ali, Syed (BMC, 2019)
Against the current global trends, in the former Soviet Union (FSU) countries HIV prevalence is on the rise. Visa-free movement across borders has facilitated migrant-associated HIV transmission within this region. Despite efforts from the governments to curtail the growing epidemic, there is still a serious need for the development of strategies that focus on high-risk behaviors and practices responsible for the continued transmission of HIV in this region. While governments of FSU countries have taken commendable steps in recent years to address hurdles at each step of the HIV care continuum, to ensure 100% antiretroviral treatment (ART) accessibility to people living with HIV (PLHIV), testing for HIV needs to be enforced widely in FSU countries. Stigma against people who inject drugs (PWID), men who have sex with men (MSM), migrants, and PLHIV need to be addressed. Finally, to avoid breaks in ART supply, FSU countries need to gain independence in funding HIV care so that the provision of ART to PLHIV is made available without interruption.
Keywords: HIV; ART; Former Soviet Union countries; FSU; Research Subject Categories::MEDICINE